Lack of school requirements and clinician recommendations for human papillomavirus vaccination - Niccolai, Linda M. (J Public Health Res, 2018)
BACKGROUND: A strong recommendation from a clinician is one of the best predictors of human papillomavirus (HPV) vaccination among adolescents, yet many clinicians do not provide effective recommendations. The objective of this study was to understand how the lack of school entry requirements for HPV vaccination influences clinicians’ recommendations. DESIGN AND METHODS: Semi-structured interviews with a purposive sample of 32 clinicians were conducted in 2015 in Connecticut USA. Data were analysed using an iterative thematic approach in 2016-2017. RESULTS: Many clinicians described presenting HPV vaccination as optional or non-urgent because it is not required for school entry. This was noted to be different from how other required vaccines were discussed. Even strong recommendations were often qualified by statements about the lack of requirements. Furthermore, lack of requirements was often raised initially by clinicians and not by parents. Many clinicians agreed that requirements would simplify the recommendation, but that parents may not agree with requirements. Personal opinions about school entry requirements were mixed. CONCLUSIONS: The current lack of school entry requirements for HPV vaccination is an important influence on clinicians’ recommendations that are often framed as optional or non-urgent. Efforts are needed to strengthen the quality of clinicians’ recommendations in a way that remains strong and focused on disease prevention yet uncoupled from the lack of requirements that may encourage delays. Additionally, greater support for requirements among clinicians may be needed to successfully enact requirements in the future.